Herpes zoster optic neuritis: a catastrophe of a disease - Mohd Zaidan, Khairun Nisa; Mohammad Razali, Amirah; Md Noh, Mohamad Syafeeq Faeez; Md Saleh, Rafidah; Mohd Isa, Muhammad (Cureus Inc., 2024)
Isolated herpes zoster optic neuritis is a rare sequelae of herpes zoster ophthalmicus (HZO). It can occur in the acute phase of HZO, or as post-herpetic complications. We report a case of a young patient with poorly controlled diabetes who developed herpes zoster optic neuritis one month after the initial skin manifestation despite completing a two-week course of oral acyclovir 800 mg five times a day. He complained of a five-day history of sudden onset, painless left eye blurring of vision. His vision over the left eye was no light perception with the presence of a left relative afferent pupillary defect. Fundus examination of the left eye revealed a swollen optic disc. Magnetic resonance imaging showed minimal fat streakiness over the left orbit. He was treated with one week of intravenous methylprednisolone 1 g/day, followed by a tapering dose of oral prednisolone (1 mg/kg/day) together with oral acyclovir 800 mg five times a day for another week. His visual acuity remained poor with a slight improvement in vision to hand motion.